Respuesta :
Answer:
y -11 = -2(x+4)
or
y = -2x+3
Step-by-step explanation:
We can use the point slope form of a line
y - y1 = m(x-x1) where m is the slope and (x1 ,y1) is a point on the line
y - 11 = -2(x- -4)
y -11 = -2(x+4)
We can rewrite it in slope intercept form
y-11 = -2x-8
Add 11 to each side
y = -2x+3
Answer:
the equation would be y=-2x+3
Step-by-step explanation:
you are given the slope and a point on this line, and the form for an equation of a line is y=mx+b, where m is the slope and b is the y-intercept. so since we know the slope already:
y=-2x+b
and we are given a point, (x, y), so plug in those numbers as x and y.
11=-2(-4)+b
now solve for b:
11=8+b
3=b
now plug in the slope, m, and y-intercept, b, back into the original equation:
so, y=-2x+3